Psychological peculiarities of gender behavior of persons of early adolescence - Палій, В. В. С.; Гранкіна, А. О. (Psychological Counseling and Psychotherapy, 2017)
The study is dedicated to investigation of peculiarities of gender behavior and gender attitudes in early adolescence. In the work represented a theoretical overview of classical and modern scientific views on the gender issue. There were analyzed structural characteristics of masculinity and femininity parameters in the personality`s sex-role sphere of adolescents. The features of young adolescents` gender attitudes had been investigated and analyzed. There was described a link between gender peculiarities of participants of the study and the type of their gender attitudes